Is there scope for expanding the optometrist's scope of practice in Singapore? – A survey of optometrists, opticians in Singapore. Issue 3 (June 2019) - George, Pradeep Paul; Yun, Olivia Chng Shih; Siow, Kalin; Saxena, Nakul; Heng, Bee Hoon; Car, Josip; Lockwood, Craig
Abstract: Purpose: In Singapore, optometrists' roles are limited compared to their counterparts elsewhere. The purpose of the survey is to investigate optometrists' current roles, views on extended roles, self-reported primary eye care knowledge, needs for continuing professional education (CPE) and views on suitable modes for CPE. Methods: Members of the Optometrist and Optician Board (OOB) were invited via email to take part in an anonymous online survey. The survey questions covered the following areas: current scope of practice, self-rated primary eye care knowledge, confidence in screening, co-managing minor eye conditions, CPE and referral behavior. Results: A total of 230 optometrists completed the survey (response rate 30%). Their current roles were limited to diagnostic refraction (92%), colour vision assessment (65%), contact lens fitting and dispensing (62%) amongst others. The average self-rated score for primary eye care knowledge was 8.2 ± 1.4; score range 1-10 (1-Very poor, 10-Excellent). Self-rated confidence scores for screening for cataract, diabetic retinopathy, chronic glaucoma and age-related macular degeneration were 2.7 ± 1.5, 3.7 ± 1.9, 4.0 ± 1.9 and 3.8 ± 1.8, respectively. 71% of the optometrists felt that they should undertake regular CPE to improve their primary eye care knowledge. Blended learning (eLearning and traditional face-to-face lectures) (46.1%) was the most preferred mode for CPE delivery. Conclusion: Optometrists in Singapore represent a skilled underutilized primary eye care provider. Though their self-reported primary eye care knowledge is high, their confidence in screening and co-managing chronic eye conditions is low. Enabling them for extended primary eye care role would require further training. Significance: Singapore ageing population has led to greater eye care demands. Task-shifting from ophthalmologists to optometrists has been proposed in the literature to handle this growing care demands. At this juncture, this study provides evidence based answers to issues revolving around optometrists' readiness for a role expansion in Singapore.